IMPLIKASI WANITA KARIR TERHADAP KEHIDUPAN KELUARGA - Erniati, Erniati; Kamridah, Kamridah; Ramang, Ramang (JURNAL SIPAKALEBBI, 2023)
The role of career women in forming a sakinah family becomes a dream and a life goal for everyone and at the same time is proof of the power and majesty of Allah SWT. However, many people mentions that the failure of children to achieve their goals is due to the negligence of career mom. Therefore, this study analyse how students whose working mother’s achievement in lectures. The metho is used in this research is descriptive qualitative by collecting data from student observations and student data surveys through Google Forms as well as interviews with working mother. The results of the study it was career women who as a mother can improve student achievement. This can be seen from the results of the survey, it was found that 92.1% said that their achievements could increase on the grounds that in general, mothers who have careers in educating their children can be wiser, democratic, and not authoritarian. Having careers, working mothers have a moderate mindset, Besides, most children imitate their parents especially whose career mothers. If their parents have a career, their children also want to be someone who has a career like their mother, so that they can increase the child's achievement motivation.